Magnetically Separable Fe3O4/γ-Fe2O3@MIL-88b(Fe) and Fe3O4/γ-Fe2O3@NH2-MIL-88b(Fe) Composites for the Photocatalytic Degradation of Congo Red Dye - Sidorov, Vladislav I.; Baimuratova, Rose K.; Korchagin, Denis V.; Ivanov, Andrey I.; Kydralieva, Kamila A.; Dzhardimalieva, Gulzhian I. (EURASIAN JOURNAL OF CHEMISTRY, 2024)
Industry-wide applications of synthetic dyes produce large amounts of dye wastewater that requires treatment. Advanced oxidation processes are considered promising, since they incorporate highly reactive hydroxyl radicals capable of oxidizing most organic pollutants, including most commonly used azo dyes, into carbon dioxide and water. In this regard, iron-based metal-organic frameworks are effective heterogeneous photocatalysts for the generation hydroxyl radicals via Fenton reaction. In this study, Fe3O4/Fe2O3@MIL-88b(Fe) and Fe3O4/γ-Fe2O3@NH2-MIL-88b(Fe) composites were obtained, where Fe3O4/γ-Fe2O3 particles enabled magnetic separation, and Fe-metal-organic frameworks (MOF) coating exhibited photocatalytic activity. These composites were characterized by elemental analysis, FTIR spectra, XRD patterns, magnetization curves, TGA profiles, nitrogen adsorption-desorption isotherms. Using ultraviolet-visible spectroscopy and Congo Red anionic azo dye (CR) as organic pollutant, composites’ adsorption kinetics were observed and their photocatalytic activities were studied. As a result, Fe3O4/γ-Fe2O3@MIL-88b(Fe) and Fe3O4/γ-Fe2O3@NH2-MIL-88b(Fe) were both capable photocatalysts for generating hydroxyl radicals from hydrogen peroxide (H2O2) through Fenton-like reaction with removal efficiencies of CR dye approaching 89 % and 95 %, respectively. Moreover, a higher photocatalytic activity was observed for Fe3O4/γ-Fe2O3@NH2-MIL-88b(Fe), supposedly, due to -NH2 group increasing the electron density on the aryl ring, which stabilized hole localization at the organic linker, increased photoexcited state lifetime and promoted electron transfer onto metal center in Fe3-μ3-O cluster